2012
DOI: 10.1007/s00701-012-1296-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of perioperative factor XIII activity levels and other haemostatic markers with the risk of postoperative intracranial haematoma in a selected cohort of neurosurgical patients

Abstract: Low platelet count can cause significant volume postoperative intracranial haematoma and in presence of multiple defects in haemostatic markers appears to be clinically useful to predict the formation of postoperative intracranial haematoma in neurosurgical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
1
4
1
Order By: Relevance
“…6 In contrast, in another series of 84 patients undergoing both elective and non-elective intracranial surgery, no difference in fibrinogen levels between patients with and without haematoma has been reported by Idris and colleagues. 7 Interestingly, in this study, fibrinogen levels did not decrease significantly and the mean postoperative fibrinogen level in the haematoma group was as high as 282 mg dl 21 . This might be explained by the different time points of postoperative blood sampling.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…6 In contrast, in another series of 84 patients undergoing both elective and non-elective intracranial surgery, no difference in fibrinogen levels between patients with and without haematoma has been reported by Idris and colleagues. 7 Interestingly, in this study, fibrinogen levels did not decrease significantly and the mean postoperative fibrinogen level in the haematoma group was as high as 282 mg dl 21 . This might be explained by the different time points of postoperative blood sampling.…”
Section: Discussioncontrasting
confidence: 46%
“…6 A more recent study, however, could not reproduce this finding. 7 We hypothesized that perioperative fibrinogen and FXIII levels would differ between patients with and without severe postoperative bleeding. The aim of this study was to assess perioperative fibrinogen and FXIII levels and also their potential association with severe postoperative bleeding in patients undergoing elective intracranial surgery.…”
Section: Accepted For Publication: 20 January 2014mentioning
confidence: 99%
“…This corresponds well to results from other studies which found POC tests predictive of perioperative and postoperative blood loss [9][10][11]. Impairment of the haemostatic system is a well-recognised risk factor for the development of postoperative intracranial haemorrhage [12] or haematoma enlargement in spontaneous or traumatic intracranial haemorrhage [13]. Although data regarding the use of POC devices in neurosurgical patients are limited, they suggest that POC testing of haemostasis may have beneficial effects in this patient population.…”
Section: Introductionsupporting
confidence: 84%
“…patients on antiplatelet or anticoagulant medication and are grouped separately, [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] while the remaining 18 studies investigated only standard coagulation tests. [97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] We considered a rating of 14 or above to be of good quality. In total, 58 studies (59%) rated 14 or above, and these are presented in ►Tables 3-8. TEG, ROTEM, and Sonoclot ►Table 3 summarizes the 17 studies that rated !14 and assessed TEG/ROTEM or Sonoclot in adults.…”
Section: Resultsmentioning
confidence: 99%